Characterization of the Asiatic Acid Glucosyltransferase, UGT73AH1, Involved in Asiaticoside Biosynthesis in Centella asiatica (L.) Urban - Kim, Ok Tae (Int J Mol Sci, 2017)
Centella asiatica (L.) Urban contains two ursane-type triterpene saponins, asiaticoside and madecassoside, as major secondary metabolites. In order to select candidate genes encoding UDP-glucosyltransferases (UGTs) involved in asiaticoside biosynthesis, we performed transcriptomic analysis of leaves elicited by methyl jasmonate (MeJA). Among the unigenes, 120 isotigs and 13 singletons of unique sequences were annotated as UGTs, including 37 putative full-length cDNAs, and 15 of the putative UGT genes were named according to the UGT committee nomenclature protocols. One of them, UGT73AH1, was characterized by heterologous expression in Escherichia coli BL21 (DE3) cells. After induction with IPTG, a total protein extract was assayed with UDP-glucose and asiatic acid. UPLC-QTOF/MS analysis showed that UGT73AH1 catalyzes the glycosylation of asiatic acid to its monoglucoside. It remains unclear whether glycosylation occurs on the triterpene C-2α, C-3β, C-23, or C-28 position. However, it is very likely that UGT73AH1 glucosylates the C-28 position, because only C-28 bears a glucose moiety in the final pathway product of asiatic acid, while C-2α, C-3β, and C-23 remain un-conjugated.